2011
DOI: 10.1002/nbm.1658
|View full text |Cite
|
Sign up to set email alerts
|

MR evaluation of response to targeted treatment in cancer cells

Abstract: The development of molecular technologies, together with progressive sophistication of molecular imaging methods, has allowed the further elucidation of the multiple mutations and dysregulatory effects of pathways leading to oncogenesis. Acting against these pathways by specifically targeted agents represents a major challenge for current research efforts in oncology. As conventional anatomically based pharmacological endpoints may be inadequate to monitor the tumor response to these targeted treatments, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 227 publications
4
88
0
1
Order By: Relevance
“…The search for biomarkers to detect cancer and to non-invasively monitor the response to treatment has led to several clinical studies evaluating the non-invasive detection of tCho for these objectives. Similar to studies in cancer cells 10 , human tumour xenograft models 10 and excised tumour tissue 11,12 , clinical studies have confirmed the activation of choline metabolism in human tumours in vivo 10,13 .…”
supporting
confidence: 61%
“…The search for biomarkers to detect cancer and to non-invasively monitor the response to treatment has led to several clinical studies evaluating the non-invasive detection of tCho for these objectives. Similar to studies in cancer cells 10 , human tumour xenograft models 10 and excised tumour tissue 11,12 , clinical studies have confirmed the activation of choline metabolism in human tumours in vivo 10,13 .…”
supporting
confidence: 61%
“…These methods include conversion of PtdCho to free choline and phosphatidic acid (PA) by phospholipase D (PLD), and the coordinated activity of phospholipase A 2 (PLA 2 ), lysophospholipase (LPL) and glycerophospholipase:phosphodiesterase (GPC:PDE) to render free choline. These enzymes have been found to be differentially expressed in some but not all cancers, and much work is still required to fully elucidate their involvement in PC production [27,28]. A number of mitogenic second messengers are released as byproducts of PtdCho cleavage (Fig.…”
Section: Choline Metabolismmentioning
confidence: 99%
“…Phosphatidylcholine (PtdCho), the most abundant phospholipid in eukaryotic cell membranes, contributes to proliferative growth and programed cell death (4). High levels of cellular phosphocholine (PC) and total choline-containing compounds [tCho: the sum of Cho, PC, and glycerophosphocholine (GPC)] have been consistently observed in cancer cells and tumor tissue and are closely related to malignant transformation, invasion, and metastasis (512). …”
Section: Introductionmentioning
confidence: 99%